GETTRUNG, NONCONVENTIONAL MUSICAL INSTRUMENT FROM WOOD - Asep Saepul Haris (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2019)
Gettrung is a non conventional musical instrument which was produced from exploration. This  instrument was made of Surian dan Mahogany woods. The shape of Gettrung is quite simple, it looks like square. The sound elements of Gettrung were the result of the parts which follow the direction based on its shapes; circle and square. Cutting the line was done until the particular part, that line was not cut to the end of the line. It means there were still some part left and it caused the vibration which produce the sound at the end (trung). This instrument was finally named as Gettrung, it comes from Get which means vibrating sound and trung which means the result of the final sound. Gettrung was categorized into percussion type. The existence of Gettrung contributes to the capability to collaborate with other instruments which have had convention (basic/standard).